2002
DOI: 10.1038/sj.onc.1205302
|View full text |Cite
|
Sign up to set email alerts
|

PAK1 primes MEK1 for phosphorylation by Raf-1 kinase during cross-cascade activation of the ERK pathway

Abstract: The serine/threonine kinase Raf-1 acts downstream of Ras in the MAPK pathway leading to ERK activation in response to mitogens. Raf-1 has oncogenic potential, but is normally controlled by a complex interplay of inhibitory and activating mechanisms. Although Raf-1 is phosphorylated in unstimulated cells, mitogens cause its membrane recruitment by Ras and subsequent phosphorylation on additional sites. Some of these events modulate Raf-1 kinase activity while others determine interactions with other proteins. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 36 publications
8
107
1
Order By: Relevance
“…PAK-1 may also phosphorylate MEK1 at Ser298 to prime MEK1 for its subsequent activation by Raf-1 ( Coles and Shaw, 2002;Park et al, 2007). We observed that PAK-1 knockdown significantly reduced both basal and insulin-stimulated ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…PAK-1 may also phosphorylate MEK1 at Ser298 to prime MEK1 for its subsequent activation by Raf-1 ( Coles and Shaw, 2002;Park et al, 2007). We observed that PAK-1 knockdown significantly reduced both basal and insulin-stimulated ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 76%
“…As MEK has been identified as one of the downstream targets of PAK-1 (Coles and Shaw, 2002;Eblen et al, 2002;Slack-Davis et al, 2003;Park et al, 2007), we next examined whether the MEK-ERK signaling pathway participates in insulin-stimulated c-Myc expression and in b-cat nuclear content and function. PD98059 is a widely used inhibitor of MEK (Alessi et al, 1995;Dudley et al, 1995).…”
Section: Mek-erk Signaling Pathway Is Involved In Insulinstimulated Cmentioning
confidence: 99%
“…Thus, alternative Ras-independent mechanisms may activate ERK during adhesion. In this regard, we and others have investigated the role of the small GTPases Rac and Cdc42 and their downstream effector PAK in activating ERK signaling during adhesion [16,17]. We and others have reported that c-Src and FAK dependent PAK phosphorylation of MEK1 may prime the ERK module for activation by low levels of Raf activity during adhesion [18], although it is possible that PAK may directly activate MEK1 in a Raf-independent fashion [19].…”
Section: Erk Activation In Response To Growth Factors and Adhesion Simentioning
confidence: 99%
“…128 Merlin, which has also recently been shown to be stabilized by the presence of an adapter protein, NGB, 76 is inactivated through Rac/Pak-mediated signaling by phosphorylation. 22 In contrast, activation through dephosphorylation is at least in part achieved through the action of MYPT-1-PP1-␦, a myosin phosphatase. 61 Myosin phosphatase activity is stimulated in part through CD44 transmembrane protein activation, providing a mechanism by which cell-cell contact may achieve growth inhibition.…”
Section: The Role Of Merlinmentioning
confidence: 99%
“…Interplay between Ras-and Rac-mediated signaling underscores the importance of merlin function at the levels of Ras and Rac. The Ras/Raf-mediated activation of downstream Mek kinases requires prior phosphorylation by Rac, 22 which may be activated by either Ras-dependent or Rasindependent mechanisms. Inhibition of Rac/Pak signaling has also been demonstrated through merlin-mediated inactivation of PI3K.…”
Section: The Role Of Merlinmentioning
confidence: 99%